Lamprey immune protein-1 (LIP-1) from Lampetra japonica induces cell cycle arrest and cell death in HeLa cells. Issue 75 (April 2018) - Chi, Xiaoyuan; Su, Peng; Bi, Dan; Tai, Zhao; Li, Yingying; Pang, Yue; Li, Qingwei
Abstract: The lamprey ( Lampetra japonic a), a representative of the jawless vertebrates, is the oldest extant species in the world. LIP-1, which has a jacalin-like domain and an aerolysin pore-forming domain, has previously been identified in Lampetra japonic a. However, the structure and function of the LIP-1 protein have not been described. In this study, the LIP-1 gene was overexpressed in HeLa cells and H293T cells. The results showed that the overexpression of LIP-1 in HeLa cells significantly elevated LDH release (P < 0.05), phosphatidylserine exposure and ROS accumulation. The overexpression of LIP-1 also had remarkable effects on the organelles in HeLa cells, while it had no effect on H293T cell organelles. Array data indicated that overexpression of LIP-1 primarily upregulated P53 signaling pathways in HeLa cells. Cell cycle assay results confirmed that LIP-1 caused arrest in the G2 /M phase of the cell cycle in HeLa cells. In summary, our findings provide insights into the function and characterization of LIP-1 genes in vertebrates and establish the foundation for further research into the biological function of LIP-1. Our observations suggest that this lamprey protein has the potential for use in new applications in the medical field. Highlights: The overexpression of LIP-1 disrupted Hela cells organelles. The overexpression of LIP-1 induced the exposure of phosphatidylserine and reactive oxygen species production in Hela cells. KEGG pathway analysis showed that the P53 signaling pathway was up-regulated in the overexpressing LIP-1 of Hela cells. LIP-1 may inhibit tumor cell viability by cell-cycle arrest.